Impact of heat treatment process on threshold current density in AlGaN-based deep-ultraviolet laser diodes on AlN substrate. (16th April 2021) - Kushimoto, Maki; Zhang, Ziyi; Sugiyama, Naoharu; Honda, Yoshio; Schowalter, Leo J.; Sasaoka, Chiaki; Amano, Hiroshi
Abstract: The electroluminescence (EL) uniformity of AlGaN-based deep UV laser diodes on AlN substrate was analyzed by using the EL imaging technique. Although nonuniform EL patterns were observed, the uniformity was improved by changing the position of the p-electrode. The threshold current density was also reduced by suppressing the inhomogeneity of the EL. Cathodoluminescence analysis revealed that the cause of the non-uniformity is the degradation of the active layer and the nonuniformity emission formed by rapid thermal annealing at high temperature after mesa structure formation.